1998
DOI: 10.1590/s0100-40421998000400002
|View full text |Cite
|
Sign up to set email alerts
|

Determinação dos hidrocarbonetos saturados e policíclicos aromáticos presentes no material particulado da atmosfera amazônica

Abstract: Recebido em 19/12/96; aceito em 22/12/97 CHEMICAL COMPOSITION OF AEROSOL COLLECTED IN THE AMAZON FOREST. It was identified and quantified several organic compounds in the atmosphere of a site into Amazon Basin with high impact of biomass burning emission. It was important to know the particulate matter composition with respect to n-alkanes and PAH associated with the particulate matter because they provided indication on the main sources contributing to airborne particles, the contribution of natural vs. man-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
(21 reference statements)
1
11
0
18
Order By: Relevance
“…In regions where biomass burning occurs, PAHs receive little attention in the literature, but one study in the Brazilian Amazon found the presence of various hydrocarbons with potentially carcinogenic effects: fluoranthene, benzo(a)anthracene, benzo(e) pyrene indeno-(cd)pyrene, dibenzo(ah)anthracene and benzo(a)pyrene 113 .…”
Section: (H)mentioning
confidence: 99%
“…In regions where biomass burning occurs, PAHs receive little attention in the literature, but one study in the Brazilian Amazon found the presence of various hydrocarbons with potentially carcinogenic effects: fluoranthene, benzo(a)anthracene, benzo(e) pyrene indeno-(cd)pyrene, dibenzo(ah)anthracene and benzo(a)pyrene 113 .…”
Section: (H)mentioning
confidence: 99%
“…Além das fontes biogênicas e antrópicas, as reações fotoquimicas na atmosfera, especialmente as envolvendo NO 3 , ozônio e radicais OH, favorecem a formação secundária de quinonas, resultando em aumento nas concentrações das quinonas presentes na fase vapor, 54 com um máximo sendo alcançado no verão. 10 Por outro lado, no periodo de inverno espera-se maiores concentrações na fase particulada(MP 2,5 ), …”
Section: Concentrações De Quinonas Na Atmosferaunclassified
“…Adicionalmente, as quinonas são formadas na atmosfera através da foto-oxidação de Hidrocarbonetos Policíclicos Aromáticos (HPA) com inúmeras espécies reativas atmosféricas. [1][2][3][4][5] Vários estudos demonstram os efeitos tóxicos e deletérios de quinonas para o organismo humano (indutor de várias doenças tais como câncer de pulmão, asma e inflamação alérgica), podendo também atuar como inibidora de enzimas importantes em sistemas celulares reparadores, causarem danos genéticos etc. [5][6][7][8][9][10][11] Por outro lado, as quinonas apresentam interesses toxicológicos e farmacoló-gicos consideráveis.…”
Section: Introductionunclassified
“…As fontes antrópicas representam o principal processo de emissão. As queimadas, a queima de combustíveis como petró-leo e seus derivados, carvão, madeira, gás de carvão, fumaça de cigarro e calefação (especialmente em países de clima temperado) são importantes fontes de HPA [8][9][10] . Segundo a literatura, os HPA podem ser usados como indicadores de fontes de emissão.…”
Section: Introductionunclassified